The Effect of Application of the Make a Match Learning Model Combined with Picture Media on Student Learning Outcomes on Ecosystem Materials at SMA Negeri 5 Banda Aceh - Zahara Khairun Nisa; Muhibbuddin Muhibbuddin; Dewi Andayani; Ismul Huda; Abdullah Abdullah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Abstract: The purpose of this research to explore the improvement of student learning outcomes who in learning process apply make a match model combined with image media in ecosystem materials. Method applied is an experiment using a pretest posttest control group design. Sample used is 60 students. The parameters measured were learning outcomes whose measurements were carried out through the provision of pre-test and post-test questions. The analysis used parametric statistical test (t test). The results analysis prove the value of Sig. 0.000 0.05, so it can be summarized from the research that the application of the make a match learning model combined with image media in ecosystem materials has an effect on improving learning outcomes.  Abstrak: Penelitian ini bertujuan mendalami peningkatan hasil belajar siswa yang dalam proses belajarnya menerapkan model make a match dipadu media gambar di materi ekosistem. Metode yang diterapkan adalah eksperimen menggunakan desain pretest postest control group. Sampel yang dipakai berjumlah 60 peserta didik. Parameter yang diukur adalah hasil belajar yang pengukurannya dilaksanakan melalui pemberian soal pre-test dan post-test. Analisis menggunakan uji statistik parametris (uji t). Hasil analisis membuktikan nilai Sig. 0,000 0,05, sehingga dapat dirangkum dari penelitian bahwa pada penerapan model pembelajaran make a match dipadu dengan media gambar pada materi ekosistem berpengaruh terhadap peningkatan hasil belajar.